Deagglomeration and Coagulation of Particles in Liquid Metal Under Ultrasonic Treatment - Olga Borisovna KUDRYASHOVA; Alexander VOROZHTSOV; Pavel DANILOV (Archives of Acoustics)
Ultrasonic processing in the cavitation mode is used to produce the composite materials based on the metal matrix and reinforcing particles of micro- and nano-sizes. In such a case, the deagglomeration of aggregates and the uniform distribution of particles are the expected effects. Although the particles can not only fragment in the acoustic field, they also can coagulate, coarsen and precipitate. In this paper, a theoretical study of processes of deagglomeration and coagulation of particles in the liquid metal under ultrasonic treatment is made. The influence of various parameters of ultrasound and dispersion medium on the dynamics of particles in the acoustic field is considered on the basis of the proposed mathematical model. The criterion of leading process (coagulation or deagglomeration) has been proposed. The calculated results are compared with the experimental ones known from the scientific literature.